Should I Stay or Should I Go? Gender Differences in Professional Employment - Kathrin Leuze; Allessandra Rusconi (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Occupational sex segregation is a persistent source of social inequalities. The increasing participation of women in tertiary education and rising female employment rates, however, have given hope that gender inequalities will decline as a result of growing female opportunities for high skill employment in the service sector, e.g. the professions. This paper asks whether such optimistic accounts are justified by comparing male and female professional career trajectories in Germany. Our main assumptions hold that, even today, strong gender differences continue to exist between public and private sector professions, which are further aggravated by different forms of family commitment. Overall, our analyses demonstrate that even among highly qualified men and women, important patterns of sex segregation are present. Aninitial horizontal segregation between public and private sectors brings about "equal, but different" career prospects, which in the phase of family formation turn into vertical segregation, promoting "different and therefore unequal" labor market chances.
Keywords: 330; professions; sex segregation; labor market outcomes; family formation; tertiary education; German